The productivity of social capital: An econometric analysis of 49 Peruvian highland communities - Henrik Wiig (University of Oslo, Department of Economics, 2003)
Many empirical studies find a partial negative effect of market integration on cooperation in traditional poor small-scale farmer communities in developing countries, blaming an erosion of collective action enhancing norms (Social Capital). This paper takes the empirical analysis one step further by estimating the effect on income. A survey on cooperation, institutions and income level was conducted by the author in 49 Peruvian highland communities in order to estimate a production function including Social Capital. None of the variables representing customary cooperation were significant in an econometric regression analysis, but various aspects of integration that can be interpreted to facilitate more modern forms of cooperation had a significant positive income effect. Communities resettling after the civil war draw on common organizational experience and emigrants represent a network to the modern society.The positive effect of the latter was significantly lower in communities with individual property rights to land. One possible explanation is the increasing tensions between emigrants and people in their communities of origin as the governmental land entitlement program proceeds. Communities with common property rights are not affected by the program and solve land disputes themselves in local assemblies.
Keywords: C21; O13; Z13; 330; Social capital; collective action; institutions; poverty; market integration; survey; Peru; Social Capital; Public Choice; Eigentum; Institutionalismus; Marktintegration; Peru